(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Family language policy (FLP) has been establishing itself as a field in the past decade. Yet, much of the scholarly debate around family multilingualism has remained within the boundaries imposed by Western-centric epistemologies. In order to address this issue, this article reviews FLP studies published between 2008 and 2017, and discusses accomplishments and limitations of recent publications. The main argument presented here is that a critical approach to family multilingualism might contribute to the development of FLP in an unexplored direction. More specifically, this paper shows how drawing on a decolonial approach allows for an express engagement with debates that have only been marginally tapped into in current FLP scholarship, for instance, the intersectional dimension of social categorisations such as social class, race, and gender. Furthermore, a decolonial approach provides a robust frame to examine transnational practices by reconciling perspectives that tend to privilege either the material basis of the economic relations of production, or the cultural domain as a locus where these relations gain meaning. Finally, a decolonial approach to family multilingualism takes a step towards redressing the extant underrepresentation of southern theories in sociolinguistics.